Additional Cover. (5th October 2020) - Georgakis, Ioannis P.; Polimeridis, Athanasios G.; Lattanzi, Riccardo
Abstract : The cover image is based on the Original Article A Formalism to Investigate the Optimal Transmit Efficiency in Radiofrequency Shimming by Ioannis Georgakis et al., https://doi.org/10.1002/nbm.4383 .